Laser Pointer Light as an Alternative Monochromatic Light Source in Diffraction Grating - Salsabila , Afiyah; Esa Rahmah , Nurul; Jansyah Yusuf , Eisha; Febriyanti , Resi; Suryadi , Ahmad (Jurnal Multidisiplin Indonesia, 2023)
Previous research only used one type of color, namely red. Then, researchers developed it by using three types of colors. In this research, we want to analyze the wavelengths produced by laser pointers of different colors, identify the distance between the grid and the screen, identify the distance between the central bright spot, and analyze the relationship between the lattice constant and the distance from the center of the light to the next light. The research method used was direct observation in the optics laboratory. The laser pointer was used as a monochromatic light source to produce a diffraction grating. Laser light sources have many colors, but we only use three colors, namely red, green and violet (purple). This experiment uses three different grating constants (????), namely a 100 slit/mm grating, a 300 slit/mm grating and a 600 slit/mm grating as well as the distance between the grating and the screen (????) (which are also different, namely 15 cm, 20 cm and 30 cm respectively). each grating constant. Based on the data that has been obtained, for red, violet and green laser light, for grating constants of 100 slits/mm, 300 slits/mm and 600 slits/mm produce the same wavelength and approaching the wavelength indicated on the laser, as well as the wavelength range of visible light.